PERLINDUNGAN HAK ASASI MANUSIA TERHADAP PEKERJA DOMESTIK DI INDONESIA - Dede Kania (Yustisia, 2015)
AbstractHistorically, domestic workers has been around a long time. Their domestically roles made them often underestimated. However, the legal protection they are still very concerned, even until now Indonesia has no law regarding the protection of domestic workers, because domestic workers act of Indonesia has not been enacted. Whereas legal protection to domestic workers is urgent considering the number of cases of abuse and violence against domestic workers, particularly female domestic workers, without any handling or legal process well. Therefore, the authors are interested in examining how the application of the theory of gender equality and inquity for domestic workers act.This research results: Firstly, the bill is needed to protect of domestic workers. Secondly, A worker of either sex is the same as other workers must be paid a fair wage and good treatment as a dignified human being. Thirdly, The aim of this act should be the process of formalizing the PRT even though the workings area of domestic workers are in domestic area. AbstrakSecara historis, pekerja rumah tangga telah ada sejak lama. Peran mereka di dalam ranah domestik membuat mereka sering diremehkan. Namun, perlindungan hukum mereka masih sangat kurang, bahkan sampai sekarang Indonesia tidak memiliki Undang-undang perlindungan pekerja rumah tangga. Perlindungan hukum bagi pekerja rumah tangga sangat mendesak keberadaannya mengingat jumlah kasus pelecehan dan kekerasan terhadap pekerja rumah tangga, terutama PRT perempuan, semakin bertambah. Oleh karena itu, penulis tertarik untuk meneliti bagaimana penerapan teori kesetaraan dan keadilan gender bagi pekerja rumah tangga.Hasil penelitian menunjukkan bahwa: Pertama, Indonesia sangat memerlukan UU untuk melindungi atau pekerja rumah tangga, sehingga RUU PRT mendesak untuk segera diundangkan. Kedua, Seorang pekerja baik perempuan maupun laki-laki mempunyai kedudukan yang sama, sehingga harus mendapatkanhak- haknya dengan baik sebagai manusia yang bermartabat. Ketiga, harus ada Formalisasi PRT walaupun kerja bidang pekerja rumah tangga berada di wilayah domestik tetapi hak-haknya sebagai pekerja harus diakui dan disamakan dengan pekerja di wilayah publik.